Transformation of the Meaning of Sholawat: Textual and Contextual Analysis of Praise for Mahalul Qiyam - Muchammad Risqi; Doni Wahidul Akbar (Al-Kalim : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
Qosidah Mahallul Qiyām has a sacred meaning, spiritually and in terms of life values. The importance of understanding the deep meaning in each verse. This study provides a deep understanding of the textual and contextual meaning in Qosidah Mahallul Qiyām. So that readers of Qosidah Mahallul Qiyām can learn lessons and increase their love for the Prophet Muhammad. This study uses a descriptive qualitative method with a literature study approach. The manuscript used in the study is the Qosidah Mahallul Qiyām book, Maulid Simtuḍḍuror Al-Habib Ali bin Muhammad bin Husein Al-Habsyi. Data collection was carried out by classifying the poems by type, then analyzing their meanings textually and contextually. In the Mahallul Qiyām qosidah in the book Maulid Simtuḍḍuror by Al-Habib Ali bin Muhammad bin Husein Al-Habsyi, it is divided into 6 aspects of meaning, including: 1. About praise for the Prophet Muhammad, 2. Welcome praise, 3. Praise for the presence of the Prophet, 4. Praise for noble servants, 5. Praise for the nature of the Prophet, 6. Praise for the intercession of the Prophet